CD105 expression on CD34-negative spindle-shaped stromal cells of primary tumor is an unfavorable prognostic marker in early breast cancer patients - Martinez, Leandro Marcelo (2015)
Several studies have confirmed that the breast tumor microenvironment drives cancer progression and metastatic development. The aim of our research was to investigate the prognostic significance of the breast tumor microenvironment in untreated early breast cancer patients. Therefore, we analyzed the association of the expression of α-SMA, FSP, CD105 and CD146 in CD34-negative spindle-shaped stromal cells, not associated with the vasculature, in primary breast tumors with classical prognostic marker levels, metastatic recurrence, local relapse, disease-free survival, metastasis-free survival and the overall survival of patients. In the same way, we evaluated the association of the amount of intra-tumor stroma, fibroblasts, collagen deposition, lymphocytic infiltration and myxoid changes in these samples with the clinical-pathological data previously described. This study is the first to demonstrate the high CD105 expression in this stromal cell type as a possible independent marker of unfavorable prognosis in early breast cancer patients. Our study suggests that this new finding can be useful prognostic marker in the clinical-pathological routine.